The antithrombin activity recovery after substitution therapy is associated with improved 28-day mortality in patients with sepsis-associated disseminated intravascular coagulation - Toshiaki Iba; Tomoki Tanigawa; Hideo Wada; Jerrold H. Levy (Thrombosis Journal, 2023)
Abstract Background Disseminated intravascular coagulation (DIC) is a common and critical complication in sepsis. Antithrombin activity, which is considered a biomarker for disease severity, was measured in septic DIC treated with antithrombin concentrates in this study. Methods We conducted a retrospective analysis of post-marketing survey data that included 1,800 patients with sepsis-associated DIC and antithrombin activity of 70% or less who were treated with antithrombin concentrates. The changes in sequential organ failure assessment (SOFA) score, DIC score, and antithrombin activity were sequentially assessed. Logistic regression analysis and receiver operating characteristic (ROC) curve analysis were performed to evaluate the performance of antithrombin activity to assess 28-day survival. Furthermore, the relationship between post-treatment antithrombin activity and survival was examined by Logistic regression analysis. Results Sex, baseline SOFA score, baseline antithrombin activities, and the presence of pneumonia and soft tissue infection were significantly associated with 28-day mortality. The area under the curve for mortality was 0.639 for post-treatment antithrombin activity, and higher than those of baseline- and delta antithrombin activities. Logistic regression analysis revealed that higher post-treatment antithrombin activity was associated with better 28-day survival. When post-treatment antithrombin activity was more than 80%, the estimated survival was 88.2%. Whereas, the survival was 74.4% when the antithrombin activity was 80% or less (P < 0.0001). However, the relationship between post-treatment antithrombin activity and 28-day survival was considerably different between patients who recovered from DIC by Day 6 compared to those who did not. Similarly, the estimated 28-day survival, based on antithrombin activity, varied among patients with high and low SOFA scores, and the calculation needs to be adjusted based on the severity of the condition. Conclusions Post-treatment antithrombin activity measurement was helpful in estimating the 28-day survival in patients with sepsis-associated DIC. However, patient outcomes vary considerably depending on factors that include baseline SOFA score, age, and baseline antithrombin activity. These variables play a substantial role in determining patient prognosis and should be considered when evaluating and interpreting the results.